2013
DOI: 10.1017/s0021859613000592
|View full text |Cite
|
Sign up to set email alerts
|

Phenological and growth response of legume cover crops to shading

Abstract: Annual medics and clovers have distinct properties in terms of usage as cover crops in Mediterranean orchards, but little is known of their capacity to adapt to the level of shading encountered on an orchard floor. A 2-year field experiment was conducted in South-Eastern Sicily to investigate the effects of withholding 0·50 of sunlight on the phenology and growth pattern of four medic and five clover accessions, focusing on traits known to be important for cover cropping. Shading delayed both seedling emergenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 40 publications
0
11
0
2
Order By: Relevance
“…Растущая обеспокоенность негативными побочными эффектами современного сельского хозяйства стимулировала необходимость поиска новых агрономических решений для улучшения экологического профиля агросистем [1,2]. В этой связи повышается роль покровных культур, которые могут повысить урожайность, а также снизить воздействие на окружающую среду в сельскохозяйственных системах [1,3].…”
Section: In the Field Studies Of 2018…2019 The Influence Of Macronutunclassified
“…Растущая обеспокоенность негативными побочными эффектами современного сельского хозяйства стимулировала необходимость поиска новых агрономических решений для улучшения экологического профиля агросистем [1,2]. В этой связи повышается роль покровных культур, которые могут повысить урожайность, а также снизить воздействие на окружающую среду в сельскохозяйственных системах [1,3].…”
Section: In the Field Studies Of 2018…2019 The Influence Of Macronutunclassified
“…Feldhake and Belesky (2005) indicated that shade tolerant cultivars of selected species would be important for successful silvopastoral management; however, actual experiments using selected species on agroforestry farms are rare. Recently, Mauro et al (2011Mauro et al ( , 2014 reported a specific adaptation to shaded environments for some legumes such as Medicago rugosa Desr., M. polymorpha L. and Trifolium spumosum. Franca et al (2016) reported about the adaptation and persistence of a grasslegume mixture for the rehabilitation of a fire prone grazed oak woodland in Sardinia and concluded that the oversowing of well-adapted pasture mixture (Trifolium yanninicum, T. brachycalycinum, Medicago polymorpha and Lullium rigidum) facilitated the recovery of the burnt area under grazing management.…”
Section: Innovations For Italian Silvopastoral Systemsmentioning
confidence: 99%
“…The growing concern about the negative side-effects of modern agriculture, has stimulated the need to find new agronomic solutions in order to improve the ecological profile of agrosystems (Carvalho Mauro et al, 2014). In this framework, cover crops can offer a valuable contribution for the agronomic management of modern agrosystems, since the positive effects that can generate on yield characteristics as well as lowering the environmental impact in farming systems (Lu et al, 2000;Djigal et al, 2012;Scopel et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In this view, cover cropping has been proposed as a pivotal tool of improving agricultural sustainability, since in the soil it has the potential to mitigate compaction and erosion (Mitchell et al, 1999;Scopel et al, 2013), increase porosity (Carof et al, 2007), improve the ability to retain and remobilise nutrients (Doltra and Olesen, 2013), enrich organic matter content, especially in the case of legume species (Stagno et al, 2008), enhance the macrofauna activity (Blanchart et al, 2006), release non-available phosphorus (Kamh et al, 1999), stimulate the generalist predator arthropod populations and heartworm communities. Moreover, cover crops generally reduce pest and weed pressure on cash crops (Den Hollander et al, 2007;Hiltbrunner et al, 2007;Pelosi et al, 2009;Chen et al, 2011;Campiglia et al, 2012) and consequently, can also represent a key option in the agronomic management of orchards in Mediterranean-type environments (Mauromicale et al, 2010;Mauro et al, 2011Mauro et al, , 2014. However, these beneficial functions, particularly relevant under organic and lowinput cropping regimes, require a knowledge about the adaptability of the species for the different agro-ecological conditions, with special attention about the changes that occur on native flora, soil properties and fruit trees (Mauro et al, 2013).…”
Section: Introductionmentioning
confidence: 99%